A Novel Method of Preparing Hexagonal Ordered Porous Alumina and Analyzing the Formation Mechanism. Issue 4 (1st October 2020) - Gao, Shuaibo; Li, Lamei; Wang, Shuai; Yan, Shu; Xing, Pengfei; Li, Xin; Kong, Jian
Abstract : In this paper, a novel method of preparing porous alumina with alumina powder and boric acid is firstly proposed and experimented, and its mechanism of the fabricating process is also investigated. Unlike traditional methods of manufacturing porous alumina including electrochemical anodization of aluminium and chemical etching, ordered porous alumina has been directly fabricated through synthesis and decomposition reactions between boric acid and alumina. Scanning electron microscopic (SEM) analysis has verified the formation of hexagonal ordered porous alumina with a homogeneous and mean diameter of ∼1 μm after sintering at high temperatures. Transmission electron microscopy (TEM) and X-ray diffraction (XRD) results show that the main component of the structure is pure alumina and no other impurities are detected, indicating an excellent corrosion resistance of the as-received product. Nano-hardness analysis shows a certain mechanical strength of the microstructure. GRAPHICAL ABSTRACT: UF0001